Should I stay or should I go? Former CEOs as monitors - Christian Andres; Erik Fernau; Erik Theissen (University of Cologne, Centre for Financial Research (CFR), 2013)
In the German two-tiered system of corporate governance, it is not uncommon for chief executive officers (CEOs) to become the chairman of the supervisory board of the same company upon retirement. This practice has been discussed controversially because of potential conflicts of interest. As a member of the supervisory board the former CEO has to monitor his successor and former colleagues, and he is involved in setting their pay. We analyze a panel covering 150 listed firms over a 10-year period. Consistent with the existence of a leniency bias, we show that firms in which a former CEO serves on the supervisory board pay their executives significantly more. We further find weak evidence that the compensation of the members of the supervisory board is also higher. Short-run event study results indicate that the announcement of the transition of a retiring CEO to the supervisory board is considered as good news. Thus, despite the increases in executive compensation we document, CEO transitions are not a cause of concern for shareholders.
Keywords: G30; G38; 330; Executive compensation; board structure; two-tiered board